The relationship of precipitation intensity, cover crops, and P management on hydrograph characteristics and water quality - Moylan, Sarah Emily (My University, 2025)
An increased frequency of intense precipitation events will impact flood potential, soil erosion, and nutrient loss from agricultural lands. Current management practices include the application of cover crops to reduce sediment loss and increase infiltration, thereby reducing surface runoff. However, the effects of cover crops and phosphorous (P) fertilizer management on water quality and runoff characteristics need to be examined to understand how these practices will perform in an environment with more frequent intense precipitation events. The objective of this study was to analyze the change in water quality and surface runoff under a range of naturally occurring precipitation intensities with the application of cover crops and P fertilizer. Runoff and water quality data were collected from the Kansas Agricultural Watershed (KAW) field laboratory in Ashland Bottoms, KS from 2015-2022 from a corn-soybean cropping rotation with edge-of-field runoff monitoring. The KAW field lab had 18 0.5-ha plots arranged in a 2x3 factorial randomized complete block design with two levels of cover (winter annual cover crops and no cover) and three levels of P fertilizer application replicated 3 times. This study used data from only two levels of P fertilization, control (CN) and spring injected P fertilizer (SI), both without cover crop (NC) and with cover crop (CC). For the SI treatments, ammonium polyphosphate (10-34-0) was subsurface applied at spring planting at a rate of 61 kg P₂O₅ ha⁻¹ from 2015 to 2019 with a slight decrease in rate to 55 kg kg P₂O₅ ha⁻¹ from 2020 to 2022. The CN plots did not receive P fertilizer. Real-time precipitation events were monitored for runoff and samples were collected and analyzed for total suspended sediment, total P, and dissolved reactive P concentrations. Mass losses of runoff, total suspended sediment, total P, and dissolved reactive P were normalized based on precipitation depth to isolate the effects of precipitation intensity. Depth measurements taken inside the flume during the runoff event were paired with precipitation data to identify the point of runoff initiation, peak flow, and runoff termination. A multiple regression analysis was completed using SAS proc glimmix (version 9.4; Cary, NC) to test if treatment effects on response variables would change under increasing precipitation intensities. The runoff ratio increased with increasing precipitation intensity for the SI-CC and the CN-NC treatments, with the greatest effect on the CN-NC treatment. Total suspended sediment load and total P load per unit of precipitation both increased with increasing precipitation intensity, with the greatest increase also occurring in the CN-NC treatment. Precipitation intensity had no effect on dissolved reactive P loss per unit of precipitation (DRPp) for the treatments receiving P fertilizer, whereas DRPp increased with increasing precipitation intensity for treatments not receiving P fertilizer. The time to runoff initiation and time to peak flow uniformly decreased with increasing precipitation intensity for all treatments. While not always significant, times to initiation and peak flow were longest in the SI-CC treatment. The time of concentration decreased for all treatments with increasing precipitation intensity. Cover crops significantly increased the time of concentration in the CN plots and significantly decreased the time of concentration in the SI plots. Peak flow increased with increasing precipitation intensity for all treatments. Cover crops and P fertilizer decreased the peak flow when compared to the CN-NC treatment with the SI-CC treatment having the smallest peak flow. Cover crops alone were shown to reduce sediment loss, total P loss, peak flow and the runoff ratio under intense precipitation. For most of these variables the addition of P fertilizer further reduces the losses except for total P loss. Under the most intense storms in this dataset plots treated with P fertilizer showed no difference in total P loss than the CN-NC treatment which was the treatment most sensitive to precipitation intensities. Dissolved reactive P was also the greatest with P fertilizer application at all intensities. Implementing these conservation management decisions should be weighed against what losses would most likely occur on the land and what local climate modeling predicts for the area. An increase in precipitation intensity is likely to occur with climate change, these management practices have shown to continue to work as a conservation effort.
Keywords: P management; Cover crop; Runoff; Precipitation intensity; Water quality